Panorama nacional sobre prevenção de drogas em contextos educacionais - Bernardo, Julia Ferreira [UNIFESP] (2019)
Despite the growing interest from researchers in the implementation and execution of drug prevention projects in educational contexts, little is known about the effectiveness of the actions developed. The lack of academic consensus on the theoretical aspects, the prevention models, the most effective approaches on the subject and the lack of comprehensive information are factors that undermine the understanding of the concept of prevention and hinder the management of feasible actions in this field. In this perspective, the identification of researchers working in this area is a possible way to integrate and share information. This study, therefore, mapped the researchers and their research on drug prevention in the educational context. The proposed method here was based on consulting the institutional CAPES repositories (Catalog of Theses and Dissertations) and CNPq (Lattes Platform) using the thesis and the dissertation research program and the scriptLattes program. From the collected data through the proposed method, three scientific articles were written, being the first article about the description of the initial mapping that identified the precursor researchers of the area in Brazil; the second article is about the expansion of the network from the academic precursor descendants; and the third article on the qualitative analysis of the identified network publications (scientific articles). The main outcomes, we found 61 precursor researchers, 143 researchers (among the precursors and their academic descendants) and 43 articles published by this network, among which 31 articles were selected for analysis. It was observed that academic collaboration occurs more among health researchers, even though this field of knowledge is multidisciplinary. The articles that discuss prevention in educational contexts are mostly about the prevalence and risk factors of adolescent drug use, not going deeper into practices and projects. This work showed that drug prevention in educational contexts is a topic that needs further study and comprehensiveness of information between the fields of knowledge involved so that the science produced at the academic level culminates in more effective practical actions.